Occupational stress experienced by nurses working in a Greek Regional Hospital: A cross-sectional study - Dimitra Chatzigianni; Andreas Tsounis; Nikolaos Markopoulos; Pavlos Sarafis (Wolters Kluwer Medknow Publications, 2018)
Background: Occupational stress is both psychologically and physically challenging and may lead to high rates of absenteeism, burnout, and turnover. Nursing is considered as one of the most stressful and demanding professions. This study aims to measure perceived stress levels among nurses in a Greek public general hospital. Materials and Methods: A cross-sectional study was conducted. A total of 157 nurses and nursing assistants took part. A self-administered questionnaire including sociodemographics and Expanded Nursing Stress Scale (ENSS) for stress assessment was used. Analysis was performed using Statistical Package for the Social Sciences version 20.0. Results: Total stress mean(SD) score ranged in medium levels [136.27 (47.80)]. The most stressful situations were dealing with death and dying [18.29 (5.59)]; patients' and their families' demands [20.90 (7.12)], and uncertainty concerning treatment [22.19 (9.07)]. Discrimination [4.40 (4.25)] and conflicts with peers [12.07 (5.10)] provoked less stress. There was a statistically significant relationship between age and total stress (F = 4.23, p < 0.001) and all distinct stressors. Nurses between 30 and 34 years expressed higher stress in all cases except patients' and their families' demands stressor. Those nurses who were divorced expressed higher stress in death and dying subscale (F = 2.93, p = 0.035). Nursing assistants expressing higher stress as far as workload (t = −2.40, p = 0.017), conflicts with physicians (t = −2.19, p = 0.033), and problems with peers (t = −2.63, p = 0.009) were concerned, compared to nurses. Conclusions: The findings of the study are in line with other researchers' findings concerning stressors among nursing personnel in Greece. Appropriate measures for the prevention and management of specific stressors must therefore be taken.